The Influence of Brand Image Service Quality and Store Atmosphere on Impulse Buying Behavior at Indomaret - Muh Wahyuddin MH (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study examines and analyses the influence of brand image, service quality, and store atmosphere on impulse buying behavior at the Indomaret Wawotobi Store. The subjects of this study were consumers at the Indomaret Wawotobi Store who had made impulsive purchases at the Indomaret Wawotobi Store, totaling 75 respondents. This study usingusesMultiple Linear Regression analysis method. The results showed that brand image, service quality, and store atmosphere significantly affected impulse buying behavior in Indomaret Wawotobi Store. The brand image partially especially impulses behavior Indomaret Wawotobi Store. Service quality has mainly changed using the behavior t the Indomaret Wawotobi Store. The store atmosphere has significantly changed behavior at the Indomaret Wawotobi Store.